Are They Still Traveling to Bali Following The Covid-19 Pandemic? Apakah Wisatawan Masih Melakukan Perjalanan ke Bali Setelah Pandemi Covid-19? - Liestiandre, Hanugerah Kristiono; Supratayasa, I Gusti Ngurah Agung; Suasapha, Anom Hery; Sumariati, I Dewa Ayu Rai; Ngelambong, Anderson (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2024)
The world has been significantly impacted by the COVID-19 epidemic, particularly in the travel and tourism sector. Even after the Covid-19 outbreak stopped, the effects in various forms continued to recur. The market segment is also affected by post-pandemic developments in the tourism industry. Geographically, changes in tourist market sectors might present new perspectives and opportunities or new challenges and risks to a tourism destination if it does not adjust quickly to these changes. This pilot study attempts to identify shifts in traveler market patterns that arise in Bali as a global travel destination following the pandemic. It illustrates how changes in market segments have occurred in this destination through tourist arrival data recorded by the National Statistics Bureau. A quantitative comparison analysis approach to the number of tourist visits reveals that there have been changes in nearly every region. The number of visitors to Bali has changed significantly in each region's tourist-generating countries. This study demonstrates that, due to various circumstances, market segment shifts have happened considerably in practically every region and every country. This study offers a crucial overview for formulating strategies and policies for growing the tourism industry after the COVID-19 outbreak.